Feminist Issues and Gender Roles in the Wonder Woman Comics - Bohatová, Andrea (Univerzita Pardubice, 2019)
The paper analyzes the Wonder Woman comics in terms of feminism and gender roles. The comics are examined from the viewpoint of the feminist literary criticism in several aspects, themes of war and mythology, bondage, her appearance, origin, and characters. It also studies its further development in the Silver, Bronze and Modern Age of comic books.
Feminismus a gender v komiksu Wonder Woman
Keywords: comics; gender; feminism; femininity; masculinity; Wonder Woman; komiksy; gender; feminismus; ženskost; mužnost; Wonder Woman